1970
DOI: 10.3329/jard.v7i1.4431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficiency of Some Indigenous Traps to Capture Rats in the Wheat Field of Bangladesh

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Throughout the rat-consuming tribes, simple, but sophisticated designs of traps exist that are made out of locally available plant materials like bamboo and string, and very rarely wire [ 5 , 30 ]. Young Adi boys from the age of 7 learn from the older menfolk how to construct such traps (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the rat-consuming tribes, simple, but sophisticated designs of traps exist that are made out of locally available plant materials like bamboo and string, and very rarely wire [ 5 , 30 ]. Young Adi boys from the age of 7 learn from the older menfolk how to construct such traps (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rodents have high breeding rate and many of them show increase in the population depending on accessibility of food (Pradhan and Talmale, 2011). Hasanuzzaman et al (2009) observed more rodents at grain filling than at the ripening stage of wheat. Sarwar et al (2011) observed that rodents established during initial stage of crop and reproduced during germinating stage and becomes abundant at the preharvest.…”
mentioning
confidence: 95%